Biennial report of the Iowa State Board of Education to the Governor and the ... General Assembly for the biennial period ending . (State Board of Education, 1910)
Contains the observations and conclusions of the Board respecting the State University of Iowa, Iowa State College of Agriculture and Mechanic Arts, Iowa State Teachers College, College for the Blind (1916-1942), and School for the Deaf (1916-1954) (varies)